Techno-economic assessment of coupling ozonation and biodegradation process for the dye wastewater treatment - Tripathi P.; Tiwari S.; Tiwari H.; Sonwani R.K.; Singh R.S. (My University, 2025)
The biological processes have been outlined as an economical and sustainable technique for the treatment of a variety of organic pollutants. However, these processes are limited when wastewater contained recalcitrant pollutants which cause a lower biodegradability index (BOD5: COD <0.2). The present study made an effort to develop a coupled system to enhance the performance of the biological processes, and subsequently treat the low biodegradability index wastewater. The performance and feasibility of the integrated system were studied for the complete mineralization of Congo red dye from wastewater. The ozonation was carried out for 25 min with an ozone dose of 69.97 mg/L to enhance the BOD5/CODratio from 0.114 to 0.44, to make the sample suitable for biological treatment. The ozonated sample was further mineralized by biodegradation. Identification of intermediate metabolites was carried out by GC–MS analysis and the end product matches closely with fragments such as 2-Amino-1-propanol (m/z = 75) and Oxaluric acid (m/z = 132). Techno–economic assessment showed that the coupling of ozonation with biodegradation could save 34 % unitary expense in comparison to a single ozonation process. © 2023 Elsevier Ltd